Lempuyang Rhizome Extract Lempuyang Rhizome Extract Microcapsule Formulation (Zingiber zerumbet) For Enhancer Appetite in Children - Rahmadevi, Rahmadevi; Lestari, Siti Marwah; Khasanah, Isti Mufidhatun Nur; Putri, Carrel Windyana (Riset Informasi Kesehatan, 2023)
Stunting is a public health problem that must be treated seriously. Findings Riskesdas showed that stunting cases were relatively stagnant at around 36.8% (2007) and reached 37.2% (2013). The problem of stunting (short children) has one of the problems of malnutrition become the focus of the Government of Indonesia. Malnutrition is often caused by a child's reduced appetite. This is very important to pay attention to when making supplement products could increase appetite. These supplements must be safe and effective to use. One of the safe products used comes from nature, such as many rhizomes grows in Indonesian soil such as: turmeric, ginger, ginger, ginger and lempuyang. Lempuyang rhizomes (Zingiber zerumbet) contain alkaloids, saponins, flavonoids, polyphenols and essential oils. This rhizome has many properties such as: tonic, anti-seizure and appetite enhancer. Supplements made from lempuyang extract are packaged in microcapsule form. Based on this, the researchers aimed to make lempuyang extract microcapsules. The supplement has been in microcapsule form used by a spray drying technique. The obtained microcapsules were evaluated using a Scanning Electron microscope, particle size analyzer which obtained 10 - 500 mm microcapsules and HPLC to determine the percentage of lempuyang extract trapped in the microcapsules (% Entrapment efficiency) of 72%.